KAJIAN PROSES KEMATANGAN BAHAN MAKANAN GUTTY KETAN MERAH DILIHAT RASANYA: RADIASI MEDAN MAGNET FREKUENSI SANGAT RENDAH - Aulia, Mashita; Alfiyanti, Naila Putri; Novianti, Vinata Dewi; Anggraeni, Firdha Kusuma Ayu; Yushardi, Yushardi; Prabandari, Audri Mely (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This study explores the novel effect of an Extremely Low Frequency (ELF) magnetic field on the durability of glutinous tape food, a traditional Indonesian food made from fermented glutinous rice. ELF magnetic field is a spectrum of electromagnetic waves with frequencies less than 300 Hz that can influence microbial activity and the chemical changes in food. The study uses a unique experimental method that exposes 20 glutinous tape samples, divided into a control group and an experimental group, each with 10 samples, to an ELF magnetic field of 1,000μT intensity for 45 minutes. The study uses a Complete Randomized Design (RAL) and analyzes the data using the One Way Anova test with LSD and Kruskal-Wallis tests using IBM SPSS Statistics 23. The results show that the experimental group’s glutinous tape samples did not experience spoilage compared to the control group’s. The study proves the ELF magnetic field's effect on the durability of glutinous tape food and provides insights for developing new food preservation techniques. The study demonstrates the innovation and applicability of using the ELF magnetic field for food durability.